Comparison of conventional and contemporary root canal disinfection protocols against bacteria, lipoteichoic acid (LTA), and lipopolysaccharide (LPS) - Alquria, Theeb A.; Alfirdous, Rayyan A.; Gupta, Swati; Santamaria, Mauro P.; Santamaria, Ingrid F.; Gomes, Ana P. M. [UNESP]; Tiradentes, Naiara [UNESP]; Silva, Eduardo G. [UNESP]; Martinho, Frederico C. (Springer Nature, 2023)
This study devised a dual-species biofilm model to investigate bacteria, lipoteichoic acid (LTA), and lipopolysaccharide (LPS) simultaneously, and compared the efficacy of conventional and contemporary disinfection protocols. Seventy single-rooted mandibular premolars were included. Fourteen teeth were negative control, and 56 teeth were infected with 3-week-old E. faecalis and E. coli GFP biofilm. Fourteen/56 teeth were positive control, with seven teeth processed for CLSM analysis and seven teeth sampled with paper points (PPs) and cryogenically ground for bacterial, LTA, and LPS analyses. Forty-two teeth were randomly divided into three groups: GWS (GentleWave system) + MIT (minimally invasive technique), PUI (passive ultrasonic irrigation) + CIT (conventional instrumentation technique), and XP-EF (XP-endo Finisher) + CIT (All, n = 14). Samples were collected before (s1) and after disinfection (s2) with PPs and after cryogenically ground (s3). CFUs were counted, and LTA and LPS were quantified with LTA-ELISA and LAL assay, respectively. XP-EF was as effective as PUI (p > 0.05). GWS + MIT was the most effective disinfection protocol against bacteria, LTA, and LPS (p < 0.05). In conclusion, PUI, XP-EF, and GWS were highly effective against bacteria, LTA, and LPS, with GWS being the most effective.